Enhanced training, employee-led deep cleans, and complete sanitation execution are effective Listeria monocytogenes controls in retail produce environments. (May 2022) - Burnett, Jack; Wu, Sophie Tongyu; Voorn, Maxwell; Jordan, Christopher; Manuel, Clyde S.; Singh, Manpreet; Oliver, Haley F.
Abstract: Our recent study on Listeria monocytogenes prevalence and persistence in 30 retail produce environments across seven U.S. states revealed that some produce departments harbored persistent L. monocytogenes isolates. Alongside food safety and sanitation experts in the retail grocery sector our research team implemented an intervention consisting of re-training on and reinforcement of sanitation standard operating procedures (SSOPs) concurrent with an employee-led deep clean in eight departments with high prevalence of L. monocytogenes . SSOPs were unchanged, apart from adding emphasis on known harborage sites. The goal was to improve the frequency and quality of sanitation tasks to their prescribed levels. Training was reinforced with regular consultative visits including weekly audits of a subset of seven departments in order to elucidate factors driving intervention outcomes. We found that our approach was able to decrease L. monocytogenes prevalence overall, however, only three of eight stores significantly reduced their prevalence. Audits revealed that the presence of foam squeegees, damaged equipment or plumbing leaks was predictive of intervention outcome. A significant reduction in prevalence on food contact surfaces (FCS) was observed; we saw no FCS positive samples post-intervention. The monthly prevalence on non-food contact surfaces wasn't significantly reduced post-intervention until the third month of sampling. Survey data demonstrated that cross-contamination risk and timing of sanitation execution were significant behavioral variables influencing L. monocytogenes prevalence. Collectively, the data indicate that a combination of enhanced retraining on sanitation and cross-contamination, employee-led deep cleans, consultative audits, a cleaning tools program, and equipment maintenance together can reduce the prevalence of L.monocytogenes in retail produce departments. Highlights: Employee-involved deep cleans and reinforcement of current SSOPs can reduce Listeria monocytogenes prevalence. Plumbing problems, foam squeegees and damaged equipment are barriers to success of this approach. Behaviors that enhance the risk of cross-contamination are correlated to L. monocytogenes prevalence. It can take up to five months of concerted effort to remediate departments with high prevalence.